Detection of Hypertension among Cardiac Diseases Inpatients at Kirkuk City Hospitals - hassan, salah (Iraqi National Journal of Nursing Specialties, 2015)
Objectives of the study: The main objective of the study is to assess the prevalence of hypertension among cardiac diseases patients and to fiend out relation ship between hypertension and cardiovascular diseases. Methodology: A descriptive study, using interviewer and questionnaire technique was conducted on cardiac diseases inpatients of clinic unite at Kirkuk and Azady hospitals from 17th ,June ,2012 to 1st, March , 2013. Non – probability (purposive) sample of (148) adult patients, (81) females and (67) males with heart disease are selected from inpatients of clinic unite at Kirkuk and Azady hospitals at kirkuk city. Questionnaire was developed to assess the items which are related to heart disease patient’s (Disease, Signs and Symptoms , Antihypertensive Drugs , Blood Pressure , and Dietary Patterns). A calibrated mercury sphygmomanometer was used to measure BP while the individual was seated and resting five minutes with the arm held at heart level. The first reading were taken in both arms; unless there was a significant difference, the right arm was used for subsequent reading. The mean of two consecutive measurements taken at two-minute intervals was recorded. Weight was measured using a calibrated scale . The study instruments consist of total (44) items, which are distributed though the following : Demographic data form consist of (10) items and questionnaire was concerned with data to evaluate the criteria of cardiac diseases patients form consist of (34) items. Results: The results of this study revealed that the mean age and standard division of study sample is (63.1 11.3), the highest percentage 52(35.1%) of age factor for heart disease patients are reported at (70-79yrs.) group .The majority of study sample are females 81( 54.7%), whereas, males are 67( 45.3%). High percent 46(31%)of participants are suffering from angina and 44(29.7%) had myocardial infarction. 40(27%) of the patients had Prehypertension (120-139/60-100) while 29(19.6%) of patients had first stage of hypertension. Recommendations : Educational programs should be designed to increase people knowledge and awareness about the life style of hypertensive heart disease patients. Booklet should be prepared and presented to the patients to advise them to leave high amount salt intake, give up exercise which is considered one of the contributing factors for hypertension.